LEGO, fishbowls, and collaboration - Rebecca Edgerley; Russell Crawford (Journal of Learning Development in Higher Education)
This article reflects on what matters in collaboration. It is widely recognised that calls for ‘collaboration’ and ‘collaborative ways of working’ abound in research, scholarship, pedagogic practices, and beyond as a desirable student skill set (Veles, 2022; McKay and Sridharan, 2023), and a way to address complexity and problem-solving (Graesser et al., 2018; Scoular et al., 2020). Now, the recent iteration of the Advance HE Professional Standards Framework (2023) cites a new dimension of practice, PSF V5, that requires fellowship claimants to explicitly evidence how they ‘collaborate with others to enhance practice’ (p. 5). However, understandings of what constitutes collaboration remain fuzzy and—specifically in the context of university professionals—somewhat underexplored (Newell and Bain, 2019). Furthermore, collaboration often falls to so called ‘third-space’ professionals, as they occupy a natural (but not always comfortable) confluence between academics, researchers, professional services, and learner communities (Veles, Carter and Boon, 2018).